Method Development for Detection and Classification of Conjunctivitis-Causing Adenoviruses in Human - Ha, Nguyen Viet; Huyen, Nguyen Thi Thu; Huyen, Do Thi Thanh; Hung, Nguyen Quang; Anh, Tran Thuy; Tuan, Hoang Anh; Sang, Nguyen Van (VNU Journal of Science: Natural Sciences and Technology, 2016)
Abstract: Conjunctivitis or “pink eye” disease caused by human adenoviruses (HAdVs) is highly contagious and persistent morbidity without any effective treatments. Types of human adenoviruses (HAdV) are also very diverse. Therefore, precise determination of HAdV-types causing conjunctivitis is important for epidemiological studies. In this study, we aimed to develop a method for detection and classification of human adenoviruses causing conjunctivitis inVietnam. The HAdV genome was extracted from clinical samples of conjunctivitis patients inVietnam. The hypervariable region 7 (HVR-7) in hexon gene of adenoviruses was amplified with the redesigned primers. HVR-7 region was then sequenced to investigate and determine the HAdV-types. The HAdV types were identified by analyzing HVR-7 sequence of the hexon gene. In this research, HAdV-3, -4, -7, -8, -37 were identified as the cause of conjunctivitis, in which serotype 8 was the predominant type, detected in 19/23 samples. Keywords: Human adenovirus, hypervariable region-7, type, conjunctivitis, PCR.